2020
DOI: 10.1111/jpn.13373
|View full text |Cite
|
Sign up to set email alerts
|

Fibrolytic enzymes improving in vitro rumen degradability of tropical forages

Abstract: During specific times of the year, especially dry seasons, tropical forages typically have poor nutritional value due to high contents of neutral and acid detergent fibres, and low crude protein in their composition, which may reduce productivity of ruminant livestock production and lead to increased enteric methane (CH4) emissions per unit of generated product in forage‐bases systems. In order to increase fibre degradability and the efficiency of energy utilisation from low‐quality forages, exogenous fibrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…(2014) describe that the addition of exogenous enzymes promotes improvements in the digestibility parameters of roughages that present a high proportion of potentially digestible fibre fraction. In the current study, the fibrolytic enzyme presents high xylanase activity, which may have acted in the most digestible fractions of sugarcane, altering or weakening the cell wall structure, without reflecting on the significant effect on in vitro NDF digestibility (Giraldo et al ., 2008; Sakita et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(2014) describe that the addition of exogenous enzymes promotes improvements in the digestibility parameters of roughages that present a high proportion of potentially digestible fibre fraction. In the current study, the fibrolytic enzyme presents high xylanase activity, which may have acted in the most digestible fractions of sugarcane, altering or weakening the cell wall structure, without reflecting on the significant effect on in vitro NDF digestibility (Giraldo et al ., 2008; Sakita et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The nutrition quality of forage diets influences ruminal functionality and digestibility. Therefore, understanding the bromatological profile of tropical grasses makes it easier to develop strategies that promote the reduction of enteric emissions (Rivera-Herrera et al 2017) and increase milk/meat productivity by area unit in livestock systems (Sakita et al 2020). The minimum protein requirement to keep a functional rumen in bovines, according to Gaviria et al (2015), is 8% CP.…”
Section: Resultsmentioning
confidence: 99%
“…They indicated that hemicellulose was preferentially degraded by the enzymatic extracts. Fibrolytic enzymes pretreating the forage can weaken and/or degrade the lignin-hemicellulose-cellulose complex of the plant 36 . This loosening effect could facilitate the attachment of microorganisms to the substrate, leading to faster growth of microbial populations and increased fiber degradation 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%